2007
DOI: 10.1182/blood-2007-06-093617
|View full text |Cite
|
Sign up to set email alerts
|

Most CML patients who have a suboptimal response to imatinib have low OCT-1 activity: higher doses of imatinib may overcome the negative impact of low OCT-1 activity

Abstract: Interpatient variability in intracellular uptake and retention (IUR) of imatinib may be due to variable function of the OCT-1 influx pump. OCT-1 activity was measured in pretherapy blood from chronic myeloid leukemia (CML) patients by calculating the difference in IUR of [14C]-imatinib with and without OCT-1 inhibition. Of patients with higher than median (high) OCT-1 activity, 85% achieved major molecular response (MMR) by 24 months, versus 45% with no more than a median (low) OCT-1 activity. Assessing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
217
4
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(237 citation statements)
references
References 26 publications
12
217
4
4
Order By: Relevance
“…SLC22A1 has been suggested to largely determine the IUR of imatinib, and its expression/activity are thought to predict the long-term outcome of chronic-phase CML cells (Thomas et al, 2004;Crossman et al, 2005;White et al, 2006White et al, , 2007White et al, , 2010Wang et al, 2008;White and Hughes, 2012). SLC22A1 transporter activity is commonly derived from the IUR of imatinib with and without "specific" SLC22A1 inhibitors such as prazosin or amantadine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLC22A1 has been suggested to largely determine the IUR of imatinib, and its expression/activity are thought to predict the long-term outcome of chronic-phase CML cells (Thomas et al, 2004;Crossman et al, 2005;White et al, 2006White et al, , 2007White et al, , 2010Wang et al, 2008;White and Hughes, 2012). SLC22A1 transporter activity is commonly derived from the IUR of imatinib with and without "specific" SLC22A1 inhibitors such as prazosin or amantadine.…”
Section: Discussionmentioning
confidence: 99%
“…SLC22A1, also referred to as organic cation transporter (OCT) 1, has frequently been implicated in the intracellular uptake and disposition of imatinib in CML cells (Thomas et al, 2004;White et al, 2006), although controversy exists with regard to its precise role (Burger et al, 2013;Nies et al, 2014). SLC22A1 transporter expression/activity toward imatinib is reported to predict the long-term outcome of chronic-phase CML (White et al, 2006(White et al, , 2007(White et al, , 2010Wang et al, 2008). Assessment of SLC22A1 transporter activity in cell lines and clinical CML samples was derived from imatinib IUR experiments in the presence or absence of SLC22A1 inhibitors such as prazosin or amantadine (Thomas et al, 2004;White et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to imatinib caused by BCR-ABL gene amplification or increased levels of mRNA can be overcome by increasing the imatinib dose [6][7][8] . More recently, it has been suggested that variations in imatinib trough plasma concentrations (C mins ) could affect cytogenetic and molecular responses in CML.…”
Section: Introductionmentioning
confidence: 99%
“…imatinib, in patients with chronic myeloid leukemia (CML) [12][13][14]. Furthermore, OCTs are determinants of the cytotoxicity of platin derivates, which is relevant for the responsiveness towards platin-containing chemotherapies [11].…”
Section: Introductionmentioning
confidence: 99%